(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The results of the research carried out in the framework of improvement of seed yield of leaf lettuce (Lactuca sativa L. var. crispa) variety samples in the soil-climatic conditions of Andijan region are presented with an in-depth scientific analysis. Also, the article describes the phenological phases and biometric indicators of leaf lettuce varieties intended for seed production